2009
DOI: 10.1128/aem.01380-09
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Ventilated Broiler Sheds: a Possible Source of AerosolizedSalmonella,Campylobacter, andEscherichia coli

Abstract: This study assessed the levels of two key pathogens, Salmonella and Campylobacter, along with the indicator organism Escherichia coli in aerosols within and outside poultry sheds. The study ranged over a 3-year period on four poultry farms and consisted of six trials across the boiler production cycle of around 55 days. Weekly testing of litter and aerosols was carried out through the cycle. A key point that emerged is that the levels of airborne bacteria are linked to the levels of these bacteria in litter. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 37 publications
(40 reference statements)
8
73
3
2
Order By: Relevance
“…The average concentration ranged from 1 to 133 cfu·m −3 of air, with most days having nondetectable concentrations. Although a variety of gram-negative bacteria have been recovered from within animal houses (Zucker et al, 2000;Chang et al, 2001;Chinivasagam et al, 2009), some researchers have indicated difficulty in cultivating these organisms at open feedlots (Wilson et al, 2002). The limited detection of airborne E. coli downwind of the freestall dairy could be caused by environmental conditions (e.g., solar radiation) that reduce overall numbers or the transformation of airborne organisms into a viable but nonculturable state.…”
Section: Airborne Bacteria and Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…The average concentration ranged from 1 to 133 cfu·m −3 of air, with most days having nondetectable concentrations. Although a variety of gram-negative bacteria have been recovered from within animal houses (Zucker et al, 2000;Chang et al, 2001;Chinivasagam et al, 2009), some researchers have indicated difficulty in cultivating these organisms at open feedlots (Wilson et al, 2002). The limited detection of airborne E. coli downwind of the freestall dairy could be caused by environmental conditions (e.g., solar radiation) that reduce overall numbers or the transformation of airborne organisms into a viable but nonculturable state.…”
Section: Airborne Bacteria and Fungimentioning
confidence: 99%
“…Bioaerosols generated at concentrated animal-feeding operations (CAFO) may cause adverse health effects such as allergy and toxicosis in animals, workers, and residents in nearby communities (Dungan, 2010). To date, most CAFO studies have investigated bioaerosols within animal housing units, near mechanical ventilation systems, downwind of the facility, or all 3 (Chang et al, 2001;Wilson et al, 2002;Schulze et al, 2006;Chinivasagam et al, 2009). The general trend is that bioaerosol concentrations are typically the greatest indoors, less near the exhaust of the ventilation systems, and decrease with distance to background concentrations within a few hundred meters of the animal production facilities.…”
Section: Introductionmentioning
confidence: 99%
“…47 Several studies have reported the presence of high levels of airborne Escherichia coli, Salmonella, and Campylobacter inside poultry houses. 29,31,[48][49][50][51][52][53] …”
Section: Littermentioning
confidence: 99%
“…Wathes et al (1986) found warm and dry temperatures of more than 30 °C increased the rapid death of aerosol E. coli (Wathes et al 1986). Studies on Australian poultry farms have reported a seasonal pattern for E. coli survival, where survival rates increase in the colder months compared to summer months (Chinivasagam et al 2009;Wathes, 1996). Another study by Chinivasagam et al (2009) suggested that high temperatures and direct sunlight reduced the level of bacteria.…”
Section: Risk and Predisposing Factors Associated With Avian Colibacimentioning
confidence: 99%
“…birds (Chinivasagam et al, 2009). A standardised management protocol in regards to farm management, drug administration and biosecurity protocols are followed on all of the chicken farms owned by the company due to the integrated system (ABARES, 2011).…”
Section: The Australian Poultry Industrymentioning
confidence: 99%